Subjective Health, School Victimization, and Protective Factors in a High-Risk School Sample. Issue 5 (June 2015) - Menrath, Ingo; Prüssmann, Marie; Müller-Godeffroy, Esther; Prüssmann, Christiane; Ravens-Sieberer, Ulrike; Ottova-Jordan, Veronika; Thyen, Ute
ABSTRACT: Objective: School victimization has adverse effects on mental and physical health. However, little is known about the influence of protective factors, socioeconomic status (SES), or a migration background (MB) on this association. The authors analyzed data from a multicenter longitudinal school study with a high proportion of pupils with a low SES and an MB. Victimization was defined as bullying or the experiences of interpersonal violence. Methods: In a cross-sectional design, 2483 pupils of secondary schools in northern Germany completed standardized questionnaires measuring families' SES, MB, school victimization, psychosomatic complaints, life satisfaction, health-related quality of life (HRQoL), and social and personal protective factors. The authors tested the association between victimization, low protective factors, low SES and MB, and subjective health parameters using linear regression models. Results: A total of 39% of the pupils reported being bullied, and 16% had experienced interpersonal violence. Victimized children reported twice as many psychosomatic problems, lower life satisfaction, and reduced HRQoL (p < .001) compared with children without victimization experiences. Regression models confirmed this association; in addition to victimization, low social and especially low personal protective factors increased the risk for low subjective health parameters. The SES and MB had no influence on the outcomes. Conclusion: The results underscore the strong association between school victimization and low subjective health factors. Strengthening pupils' self-efficacy and a supportive school climate can diminish the health consequences of victimization.